PERSEPSI MASYARAKAT TERHADAP DAMPAK LINGKUNGAN PADA USAHA PETERNAKAN AYAM RAS PEDAGING (BROILER) DI KOTA BANJARBARU - Heri Purwanto; Emmy Sri Mahreda; Danang Biyatmoko; Abdi Fithria (Universitas Lambung Mangkurat, 2013)
Broiler poultry farms in the residential area of Banjarbaru City has the potential to cause negative impacts of pollution in the form of chicken droppings (faeses), the smell of ammonia, the emergence of a lot of flies and rats, and the threat of outbreaks of diseases that can be transmitted from poultry to humans (zoonoses). Based on the above issues, it is necessary to investigate the public perception and the factors influencing the perception of the environmental impact of broiler poultry farms in Banjarbaru. This perception problem is very essential to be investigated in order to determine the level of public perception and the factors that influence it. This study employed the data analysis with descriptive statistics that were used to describe the public perception and the factors that influence the perception of the environmental impact of broiler poultry farms in Banjarbaru. The results of this study indicated that the perception of 23 respondents (72%) was negative while the perception of 9 respondents (28%) was positive. These results rejected the initial hypothesis (H0), which suspected that the public perception of the environmental impact of broiler poultry farms was positive and received the first hypothesis (H1), which suspected that the public perception of the environmental impact of broiler poultry farms was negative. The significant factors influencing public perception of the environmental impact of broiler poultry farms were the education, the employment, the level of public health and the air pollution/ the odor of chicken droppings with the significance probability value for each factor was 99% or 0.000 (p <0.05), whereas the variable information (x5) and the environmental impact (x6) were not significant, which was indicated by the probability value of the significance of each factor that was 0.107 (p> 0.05) and 0.238 (p> 0,05).